Multicentre standardisation of chest MRI as radiation-free outcome measure of lung disease in young children with cystic fibrosis - Wielpütz, Mark Oliver; Stackelberg, Oyunbileg von; Stahl, Mirjam; Jobst, Bertram; Eichinger, Monika; Puderbach, Michael; Kauczor, Hans-Ulrich; Mall, Marcus A. (Journal of cystic fibrosis, 2018)
Background - A recent single-centre study demonstrated that MRI is sensitive to detect early abnormalities in the lung and response to therapy in infants and preschool children with cystic fibrosis (CF) supporting MRI as an outcome measure of early CF lung disease. However, the feasibility of multicentre standardisation remains unknown. - Objective - To determine the feasibility of multicentre standardisation of chest MRI in infants and preschool children with CF. - Methods - A standardised chest 1.5T MRI protocol was implemented across four specialised CF centres. Following training and initiation visits, 42 infants and preschool children (mean age 3.2±1.5years, range 0-6years) with clinically stable CF underwent MRI and chest X-ray (CXR). Image quality and lung abnormalities were assessed using a standardised questionnaire and an established CF MRI and CXR score. - Results - MRI was successfully performed with diagnostic quality in all patients (100%). Incomplete lung coverage was observed in 6% and artefacts also in 6% of sequence acquisitions, but these were compensated by remaining sequences in all patients. The range of the MRI score in CF patients was similar across centres with a mean global MRI score of 13.3±5.8. Cross-validation of the MRI against the CXR score revealed a moderate correlation (r=0.43-0.50, p<0.01). - Conclusion - Our results demonstrate that multicentre standardisation of chest MRI is feasible and support its use as radiation-free outcome measure of lung disease in infants and preschool children with CF.
Gesehen am 17.03.2020